1993
DOI: 10.1002/1097-0142(19930815)72:4<1171::aid-cncr2820720407>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin use, cancer, and polyps of the large bowel

Abstract: Background. The effect of aspirin use on 490 patients with cancer of the colon, 340 with cancer of the rectum as the first primary site, and 212 patients with polyps having no coexisting malignancies was compared with that of two groups of control subjects that consisted of 524 hospital patients having no cancers and no diseases of the digestive organs and 1138 healthy visitors to the screening clinic. All subjects entered Roswell Park Cancer Institute between 1982 and 1991. Methods. After adjustment for adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
61
2

Year Published

1994
1994
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(66 citation statements)
references
References 25 publications
3
61
2
Order By: Relevance
“…27,28 Other epidemiological studies generally have found consistent dose relationships for both adenoma [29][30][31][32][33] and cancer. 13,29,[34][35][36][37][38] Although short-term use of aspirin appears to reduce risk of adenoma, [1][2][3]32 we observed that an overall reduction in risk of cancer required more than five years of use. However, because we did not collect data on the number of years of aspirin use at study baseline, duration of use was probably somewhat underestimated.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…27,28 Other epidemiological studies generally have found consistent dose relationships for both adenoma [29][30][31][32][33] and cancer. 13,29,[34][35][36][37][38] Although short-term use of aspirin appears to reduce risk of adenoma, [1][2][3]32 we observed that an overall reduction in risk of cancer required more than five years of use. However, because we did not collect data on the number of years of aspirin use at study baseline, duration of use was probably somewhat underestimated.…”
Section: Discussionmentioning
confidence: 67%
“…Further studies should examine the potential for a differential effect of aspirin based on anatomic location which may be related to differences in the molecular characteristics of tumors. 41 Although previous studies have demonstrated an inverse relationship between aspirin and colorectal cancer, 7,8,14,29,[35][36][37][38][39][40][42][43][44][45][46][47][48][49][50][51][52][53][54] the present study differs in several important ways. First, because we collected detailed, updated information on aspirin at a range of doses over 18 years of follow-up, we were able to evaluate long-term use across a broad range of intake.…”
Section: Discussionmentioning
confidence: 95%
“…There was no way to ascertain whether or not those individuals who refused to complete the instrument differed from participants with respect to aspirin use. Nevertheless, previous studies that used the PEDS database and looked at effects of aspirin on variety of cancer sites like ovary, colon, pancreas, breast, nonHodgkin lymphoma and lung 30,32,[68][69][70][71] consistently replicated established epidemiological associations. Moreover, the descriptive characteristics of the subjects (Table I) are consistent with well documented reports in the literature, [10][11][12] suggesting that the results may be generalized to a larger population.…”
Section: Discussionmentioning
confidence: 99%
“…There is substantial evidence of an inverse association between use of nonsteroidal anti-inflammatory drugs (NSAIDs) and the risk of colorectal cancer (Kune et al, 1988;Rosenberg et al, 1991Rosenberg et al, , 1998Thun et al, 1991Thun et al, , 1993Suh et al, 1993;Muscat et al, 1994;Peleg et al, 1994;Schreinemachers et al, 1994;Giovannucci et al, 1995;Smalley et al, 1999;Baron and Sandler, 2000;Coogan et al, 2000;Langman et al, 2000;Rodrigues and Huerta-Alvarez, 2001). A protective effect was initially observed in experimental studies and has been seen in epidemiologic studies of both cohort and casecontrol designs.…”
mentioning
confidence: 99%